1998
DOI: 10.1006/clad.1998.0064
|View full text |Cite
|
Sign up to set email alerts
|

The Logical Basis for the use of Continuous Characters in Phylogenetic Systematics

Abstract: It has been argued that continuous characteristics should be excluded from cladistic analysis for two reasons: because the data are considered inappropriate; and because the methods for the conversion of these data into codes are considered arbitrary. Metric data, however, fulfill the sole criterion for inclusion in phylogenetic analysis, the presence of homologous character states, and thus cannot be excluded as a class of data. The second line of reasoning, that coding methods are arbitrary, applies to gap a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 10 publications
0
80
0
8
Order By: Relevance
“…As Maddison et al (1984), Felsenstein (1988), Swofford and Olson (1990), Thiele (1993), Lieberman (1995) and, most recently, Rae (1998) have pointed out, there is no intrinsic difference between qualitative and morphometric characters as far as cladistics is concerned. The only criterion a character must fulfill for use in a cladistic analysis is that its states are homologous, and morphometric characters can meet this criterion as well as qualitative characters (Rae, 1998). The artificiality argument can also be easily refuted, for coding is no more artificial than is the decision to break up into discontinuous states what is, with few exceptions, continuously distributed morphology.…”
Section: Character State Data Matrixmentioning
confidence: 95%
“…As Maddison et al (1984), Felsenstein (1988), Swofford and Olson (1990), Thiele (1993), Lieberman (1995) and, most recently, Rae (1998) have pointed out, there is no intrinsic difference between qualitative and morphometric characters as far as cladistics is concerned. The only criterion a character must fulfill for use in a cladistic analysis is that its states are homologous, and morphometric characters can meet this criterion as well as qualitative characters (Rae, 1998). The artificiality argument can also be easily refuted, for coding is no more artificial than is the decision to break up into discontinuous states what is, with few exceptions, continuously distributed morphology.…”
Section: Character State Data Matrixmentioning
confidence: 95%
“…continuous) characters are fundamentally different from 'discrete' qualitative characters and should be excluded from phylogenetic analyses (e.g., Crisp and Weston, 1987;Pimentel and Riggins, 1987;Cranston and Humphries, 1988;Crowe, 1994). However, such a position has been rebutted by numerous authors (e.g., Baum, 1988;Chappill, 1989;Thiele, 1993;Rae, 1998;Swiderski et al, 1998;MacLeod, 2002) who have shown that qualitative characters are invariably points along a continuous scale of variation yet, confusingly, are described in a manner that merely implies 'discreteness' (e.g., 'moderately curved', 'curved', 'highly curved', etc.). As MacLeod (2002, p. 103) has wryly noted, even a seemingly unambiguous and so-called 'discrete' character such as colour, which is sometimes used by those who criticise the use of metric characters (e.g., Pimentel and Riggins, 1987), is actually a ratio-scale variable based on the frequency spectrum of reflected light.…”
Section: Character Codingmentioning
confidence: 99%
“…For instance, while a character such as 'length' could arbitrarily be divided into 'long', 'medium' and 'short' character states via qualitative assessment, variations of such a character will be evident both within and between OTUs. If such states overlap, or even come close to overlapping, character state assignation will inevitably become increasingly subjective (Rae, 1998). Conversely, the use of morphometric data allows character state assignations to be made on a non-arbitrary basis via statistical analysis of character variation and difference, even in the event of some degree of overlap (e.g., Thorpe, 1984).…”
Section: Character Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…While this interest was driven in part by the invention of new nondestructive imaging techniques, particularly computer tomography (CT), in combination with sophisticated computer graphic applications (see Spoor et al 2000 for a review), modern cladistic analyses also require more detailed annotations of the paranasal sinuses to elucidate the detailed evolution of the craniofacial skeleton (Rae 1998(Rae , 1999. Although our knowledge about morphology, growth, and development of the paranasal sinuses of some non-human primates has increased considerably (Rae and Koppe 2004), access to CT for this sort of study is not only limited but also expensive.…”
Section: Introductionmentioning
confidence: 99%